2016
DOI: 10.1186/s13058-016-0671-y
|View full text |Cite
|
Sign up to set email alerts
|

Male breast cancer in BRCA1 and BRCA2 mutation carriers: pathology data from the Consortium of Investigators of Modifiers of BRCA1/2

Abstract: BackgroundBRCA1 and, more commonly, BRCA2 mutations are associated with increased risk of male breast cancer (MBC). However, only a paucity of data exists on the pathology of breast cancers (BCs) in men with BRCA1/2 mutations. Using the largest available dataset, we determined whether MBCs arising in BRCA1/2 mutation carriers display specific pathologic features and whether these features differ from those of BRCA1/2 female BCs (FBCs).MethodsWe characterised the pathologic features of 419 BRCA1/2 MBCs and, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 25 publications
7
71
0
6
Order By: Relevance
“…23 Pathogenic variants were defined as previously described. 24 All participating studies have been approved by local ethical review committees.…”
Section: Methodsmentioning
confidence: 99%
“…23 Pathogenic variants were defined as previously described. 24 All participating studies have been approved by local ethical review committees.…”
Section: Methodsmentioning
confidence: 99%
“…Up until this point, the vast majority of data on men have come from smaller retrospective studies with limited power to effectively support treatment selection and survivorship issues. There is a suggestion that breast cancer behaves differently in men compared with women, but this is not well understood nor do we know how to act on these differences (72,73). For example, in a study comparing Oncotype DX scores among men and women, although many similarities were noted in scores overall, the mean expression of estrogen and progesterone receptors were higher in men, as were proliferation genes such as Ki-67 (73).…”
Section: Male Patientsmentioning
confidence: 99%
“…It also shows that genetic tests were performed in some men several years after their diagnosis. Studies of the pathological features of BRCA1/2 MBC tumours showed that these tumours display distinct characteristics compared with BRCA1 / 2 female breast cancer tumours (eg, high histologic grade in BRCA2 MBC patients), which suggested greater biological aggressiveness . Although it is not directly proven for MBC caused by BRCA1/2 mutations, it might be the case that some patients in this specific group were not tested because they did not survive the disease.…”
Section: Discussionmentioning
confidence: 99%